Sirolimus therapy may cause cardiac tamponade. (29th November 2012) - Bertrand, Dominique; Desbuissons, Geoffroy; Pallet, Nicolas; Debure, Alain; Sartorius, Albane; Anglicheau, Dany; Mamzer, Marie‐France; Legendre, Christophe; Sberro‐Soussan, Rebecca
Summary The side‐effects associated with the immunosuppressive drug sirolimus are numerous and constitute a major limitation for its use in renal transplantation. In this study, we describe two cases of renal transplant recipients treated with sirolimus who developed pericardial tamponade associated with interstitial pneumonia, proteinuria, microcytic anemia and, in one case, lymphocytic meningitidis. An extensive search for infectious agents was negative, and all symptoms disappeared after sirolimus interruption. Therefore, this case demonstrates for the first time that sirolimus can cause pericardial tamponade as well as lymphocytic meningitidis.